Spatial mobility and large-scale resource extraction: An analysis of community well-being and health in a copper mining area of Zambia. (March 2022) - Farnham, Andrea; Winkler, Mirko S.; Zabré, Hyacinthe R.; Divall, Mark J.; Fink, Günther; Knoblauch, Astrid M.
Highlights: We conducted household surveys near a large copper mine in Zambia in 2015 and 2019. 40% of the study population migrated into the area within 5 years of the survey. Migrants were younger, more educated, and more likely to work in the mine. Malaria and stunting were significantly reduced in migrants to the area. Household wealth and employment was higher in those who migrated or were resettled. Abstract: We examine population mobility around a newly-developed large-scale copper mine in Zambia and analyse how socioeconomic and health indicators differed amongst migrants, resettled households, and non-mobile local (e.g. non-migrant/-resettled) populations. Two cross-sectional household surveys in 2015 and 2019 collected quantitative data on health, socioeconomic indicators, and resettlement and migration status. A wealth index for the pooled sample ( N = 990 households) was computed using a simplified list of household assets adapted from the Zambia Demographic and Health Survey. Logistic regression models were conducted to assess associations with health outcomes. In-migrants were younger than non-mobile locals (mean age of household head 33.9 vs. 37.7 years), more highly educated (34.3% of household heads completed secondary school vs. 7.3%), had higher employment (43.8% vs. 15.8%), and higher mean wealth (3.6 vs. 3.0). The odds of having a child <5 years diagnosed with malaria (OR: 0.53, 95% CI: 0.40, 0.71) or classified as stunted (OR: 0.66, 95% CI: 0.50, 0.87) were significantly lower for migrants during the construction phase, even after adjusting for family wealth score. Migrant and resettled households had greater wealth and assets even after adjusting for age, education, and employment, suggesting spatial mobility is associated with improved socioeconomic status and disease prevention.